Modified Bilateral Filter for Feature Enhancement in Mesh Denoising - Hyeon-Deok Han; Jong-Ki Han (IEEE Access, 2022)
Mesh models resulting from scanners are inevitably noisy; hence, removing the noise in scanned meshes becomes an essential task in the services using three-dimensional mesh models. Filtering-based methods are simple but have some constraints in eliminating noise because they degrade the features in the mesh models while removing the noise. In this study, we design a feature enhancement filter that is combined with a conventional denoising filter to remove the noise while enhancing the features. The designed enhancement filter is applied only to the feature areas in the mesh model. Results from experiments on synthetic and natural scanned models validate that the proposed method can restore false features by integrating conventional filtering-based methods, and outperforms other state-of-the-art methods.